In vitro and in vivo evaluation of clastogenicity of second-line antitubercular drug loaded PLGA nanoparticles. (July 2021) - Pandey, Avaneesh Kumar; Kumar, Rajendra; Shafiq, Nusrat; Kondel, Ritika; Garg, Shanky; Negi, Harish; Arora, Sunil Kumar; Varma, Neelam; Malhotra, Samir
Sustained release nanoformulations of second line antitubercular drugs levofloxacin and ethionamide had shown promise in pharmacokinetics and acute and sub-acute toxicity studies. The present study evaluated the clastogenicity potential of the nanoformulations of these antitubercular agents. Clastogenicity was evaluated by (a) in vitro micronucleus assay (b) in vivo micronucleus assay in Swiss albino mice and (c) sister chromatid exchange (SCE) in CHO cell lines. Ethionamide and levofloxacin loaded nanoparticles were 312 ± 64 nm and 245 ± 24 nm in size respectively and drug encapsulation was 35.2 ± 3.1% w/w and 45.6 ± 9.4% w/w, respectively. The frequency of MN-NCE/1000 NCE and MN-PCE/1000 PCE were significantly reduced in mice treated with ethionamide nanoparticle (3.5 ± 0.9, 13.8 ± 16.68) and levofloxacin nanoparticles (5.6 ± 2.7, 16.7 ± 12.7) compared to the mice treated with free ethionamide (11.5 ± 4.1, p = 0.23 and 45.19 ± 19.21, p = 0.38) and free levofloxacin (14.7 ± 1.88, p < 0.0001 and 54.6 ± 18.1, p = 0.0017), respectively. For in vitro, micronucleus assay frequencies of micronuclei per thousand bi-nucleated cells (MN-BN/1000 BN) was 188.3 ± 20.20 and 148 ± 20.42 for ethionamide and levofloxacin nanoparticles as compared to 232.6 ± 16.04 (p = 0.52) and 175 ± 5.56 (p = 0.45) for free ethionamide and levofloxacin, respectively. The average number of SCE per cell for nanoformulation of ethionamide were not different from that of free drug (4.9 ± 0.51 vs 4.1 ± 0.55, p = 0.86). The SCE per cells were not significant difference for nanoformulation of levofloxacin (2.33 ± 1.36 vs 5.46 ± 0.25, p = 0.88). In vitro and in vivo assays have shown relatively less clastogenic potential of equivalent dose of ethionamide nanoparticles as compared to the conventional formulation.